Advances in myopia research anatomical findings in highly myopic eyes - Jonas, Jost B.; Wang, Ya Xing; Dong, Li; Guo, Yin; Panda-Jonas, Songhomitra (Eye and Vision, 2020)
The goal of this review is to summarize structural and anatomical changes associated with high myopia.